Chronic graft‐versus‐host disease in pancreas after kidney transplant recipients – An unrecognized entity. Issue 2 (20th September 2020) - Singh, Prince; Razonable, Raymund R.; Lorenz, Elizabeth C.; DiCaudo, David J.; Sukov, William R.; Bridges, Alina G.; Alkhateeb, Hassan B.; Hogan, William J.; Klomjit, Nattawat; Thirunavukkarasu, Sorkko; Amer, Hatem; Kudva, Yogish C.; et al.
Abstract : Graft‐versus‐host disease (GVHD), a common complication after peripheral blood stem cell or bone marrow transplantation, rarely occurs in kidney and pancreas transplant recipients. The true incidence may be confounded by the rarity of the disorder, with a resultant lack of appreciation of the diagnosis as a potential cause of common clinical manifestations such as cytopenias and immune dysfunction. Reports of GVHD in kidney and pancreas transplant recipients almost uniformly describe patients in the early posttransplant period (days to months) with the typical manifestations of acute GVHD involving the skin, liver, and intestines. In contrast, reports of solid organ transplant recipients with clinical features more consistent with chronic GVHD (cGVHD) are lacking, raising concern of underrecognition of this severe complication. Occurrence later after transplant may be even more likely to result in lack of recognition. We report 2 cases of possible cGVHD occurring in recipients of pancreas after kidney transplantation, which were diagnosed at 5.5 and 42 months after pancreas transplant. Both patients presented with severe pancytopenia, multiple opportunistic infections, and features suggestive of cGVHD. Transplant professionals should be aware of the possibility of acute and cGVHD in pancreas after kidney transplant recipients and be able to recognize the clinical manifestations. Abstract : The authors describe 2 cases of fatal chronic graft‐versus‐host disease in pancreas after kidney transplant recipients diagnosed in the setting of severe infections with profound pancytopenia.